INVENTARISASI TUMBUHAN HERBAL YANG DI GUNAKAN SEBAGAI TANAMAN OBAT KELUARGA - Harefa, Darmawan; Murnihati Sarumaha; Amaano Fau; Kaminudin Telaumbanua; Fatolosa Hulu; Baziduhu Laia; Anita Zagoto; Agustin Sukses Dakhi (Universitas Nias Raya, 2023)
This service aims to inventory the types of herbal plants used as family medicinal plants in Hilimondrege Raya Village. This service is a type of qualitative research with descriptive methods with a total of 5 respondents. Data collection by observation, interviews, documentation. Based on the findings of this service, it can be concluded that there are 15 plant species used by the people of Hilimondrege Raya Village as family medicinal plants, namely Cocor duck (Kalanchoe Pinnata), Soursop (Annona muricata), Ila-lang (Imperata cylindrica), Bandotan (Ageratum conizoides) , Earrings (Acalypha australis), Ginger (Zingiber officinale), Cat's whiskers (Orthosiphon aristatus), Turmeric (Curcuma domestica), Mahkota dewa (Phaleria macrocarpha), Guava (Psidium guajava), Lime (Citrus aurantifolia), Areca nut (Areca catechu), Cardamom (Amomum compactum), Water henna (Impatiens balsamina), Pulutan (Urena lobata). Suggestions for this research are expected to maintain the habit of using plants as medicine, and also teach children and young people about natural medicine. Natural treatment should be a source of knowledge, understanding and insight for the people of Hilimondrege Raya Village.